PEMBELAJARAN IPA FISIKA BERBASIS OUTDOOR-INQUIRY UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA DIKELAS VIII SMPN 5 PEKANBARU - charistia, Sofian; ', Zulhelmi; ', Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to described and know the effectiveness of the improvement Physics process skills in the class VIII Junior High School 5 Pekanbaru. approach study outdoor inquiry in light materials. The research was conducted from February 2016 until mei 2016 by population all of students in class VIII junior high school 5 Pekanbaru.The plan in this research is design Intact Group comparasion, with the class VIII8 as an experimental class and class VIII7 as the control class. The research instrument used is Physics process skills achievement test array of aspect: formulate, plan, hypothetical, conclude and communicate. The results of the research indicated of all aspect 86.8% in very well categories and very efectively in the class VIII8 and other hand 80.97% in good category and effectively. As conclution approach study outdoor inquiry can improve the Physics process skills of student junior High School 5 Pekanbaru.Keywords: Outdoor Iinquiry, Process Skills, Light.